Associations between endothelial dysfunction and clinical and laboratory parameters in children and adolescents with sickle cell anemia. - Rozana Santos Teixeira; Regina Terse-Ramos; Tatiane Anunciação Ferreira; Vinícius Ramos Machado; Marya Izadora Perdiz; Isa Menezes Lyra; Valma Lopes Nascimento; Ney Boa-Sorte; Bruno B Andrade; Ana Marice Ladeia (PLoS ONE)
Background Hematological changes can drive damage of endothelial cells, which potentially lead to an early endothelial dysfunction in patients with sickle cell anemia (SCA). An association may exist between endothelial dysfunction and several clinical manifestations of SCA. The present study aims to evaluate the links between changes in endothelial function and clinical and laboratory parameters in children and adolescents with SCA. Methods This study included 40 children and adolescents with stable SCA as well as 25 healthy children; aged 6-18 years. All study subjects were evaluated for endothelial function using Doppler ultrasonography. In addition, a number of laboratory assays were performed, including reticulocyte and leukocyte counts as well as measurement of circulating levels of total bilirubin, C-reactive protein (CRP), glucose, lipoproteins and peripheral oxyhemoglobin saturation. These parameters were also compared between SCA patients who were undertaking hydroxyurea (HU) and those who were not. Results Flow-mediated vasodilation (FMD) values were found to be reduced in SCA patients compared with those detected in healthy controls. SCA individuals with lower FMD values exhibited higher number of hospital admissions due to vaso-occlusive events. Additional analyses revealed that patients who had decreased FMD values exhibited higher odds of acute chest syndrome (ACS) episodes. A preliminary analysis with limited number of individuals failed to demonstrate significant differences in FMD values between SCA individuals who were treated with HU and those who were not. Conclusions Children and adolescents with SCA exhibit impaired endothelial function. Reductions in FMD values are associated with ACS. These findings underline the potential use of FMD as screening strategy of SCA patients with severe prognosis at early stages.